Levodopa/dopa decarboxylase inhibitor associated microscopic colitis: An under-recognized drug reaction. (May 2021) - Ong, Tien Lee; Dal, Shoaib; Martin, Andrew J.; Chang, Florence CF.; Williams, Laura J.; Babu, Sangamithra; Mahant, Neil; Morales-Briceno, Hugo; Fletcher, Naomi; Nankervis, Jane; Robbie, Melissa; Fung, Victor S.C.
Abstract: Background: Microscopic colitis is a form of inflammatory bowel disease characterized by profuse non-bloody watery diarrhea. Macroscopic abnormality is not present on colonoscopy, and it requires biopsy for diagnosis. Few cases have been attributed to levodopa/dopa-decarboxylase inhibitor therapy. Method: A retrospective cohort study of 21 patients on levodopa/benserazide and one patient on levodopa-carbidopa intestinal gel with clinically suspected or biopsy proven microscopic colitis. Results: All 21 patients on oral levodopa/benserazide had resolution of diarrhea with cessation of the medication. Four patients discontinued levodopa permanently. Two were rechallenged with levodopa/benserazide without symptom recurrence. One patient on oral levodopa/carbidopa developed diarrhea only with intermittent dispersible levodopa/benserazide. 14 were switched to levodopa/carbidopa with resolution of diarrhea in 9 but symptom recurrence in 5. One patient on oral levodopa/benserazide developed profuse diarrhea when switched to levodopa-carbidopa intestinal gel. Of 7/22 patients who had colonoscopy and biopsy, 5 had histopathological proven microscopic colitis. Conclusion: levodopa/dopa-decarboxylase inhibitor induced microscopic colitis may be more common than previously suspected, with the potential to affect treatment compliance and therapeutic options. Highlights: Microscopic colitis should be suspected in any PD patient with unexplained acute, subacute, or chronic, non-bloody or watery diarrhea on levodopa/dopa decarboxylase therapy. Following the exclusion of other etiologies and if clinically significant, a trial of substitution with an alternative levodopa/dopa decarboxylase therapy should be considered as the initial treatment strategy, being mindful of the potential impact on parkinsonian symptoms. A carefully supervised trial of withdrawal may be required as a last resort. If diarrhea persists, colonoscopy and random colonic biopsy should be performed even if the endoscopic appearance is normal.